The Board of Directors' Criminal Liability for Companies Which Declared On Bankruptcy - Raditya Triatmaji Pramana; Bambang Dwi Baskoro (Jurnal Daulat Hukum, 2021)
Bankruptcy is regulated in Act No. 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU). In the regulation, the company is declared bankrupt, meaning that when the debtor (debt owner) has two or more creditors (debtors) who do not pay debts that are due and can be collected (cause of bankruptcy). The responsibility of the Board of Directors whose company is experiencing bankruptcy is in principle the same as the responsibility of the Board of Directors whose company is not experiencing bankruptcy. Bankruptcy status applies when there is a decision of the Commercial Court, whether it comes from the application itself or one or more creditors. After being declared bankrupt, the court decided to sell all of the company's assets, the proceeds of which were used to pay the debtors' obligations that were already bankrupt to the creditors. Based on the aforementioned background, a problem can be drawn as follows: What is the liability of the directors who are declared bankrupt? How can the board of directors be declared negligent or wrong which results in the corporation being declared bankrupt? The approach method used in writing this law is normative juridical or also called doctrinal law research. The research specification in this writing is descriptive-analytic. Based on the results of the research, it can be concluded that the Board of Directors is not personally responsible for the actions committed for and on behalf of the Company based on their authority. This is because the actions of the Board of Directors are seen as actions. The Board of Directors is said to have been wrong or negligent which resulted in the Company being declared bankrupt, namely the lack of good faith by the directors to pay off debts to creditors. The Board of Directors neglected to pay off debts to creditors.